Literature review of potential materials for the construction of an alternative flat-plate solar collector (Research, Society and Development, 2024)
Through systematic review method the article presents the potential of existing solar energy in Mozambique for use in water heating with the integration of thermal energy storage systems that are currently being investigated. It emphasizes the need for affordable materials in building solar collectors for Mozambique’s homes, leveraging the country’s solar potential to reduce electricity consumption and environmental impact for sustainable development. It explores current research on thermal energy storage systems for solar water heating and reviews alternative materials for solar collectors based on their properties, cost, and availability. The importance of thermal energy storage in solar collectors for efficiency and load balancing is highlighted., it discusses and list the potential alternative materials for the construction of flat plate solar thermal collectors from roofing material, frame, absorber, pipes, and heat storage material according to their thermophysical properties, costs, and availability in the Mozambican market in the context of industrialization.